ANALISIS STRATEGI PEMASARAN BISNIS EKSPOR IMPOR PERUSAHAAN FREIGHT FORWARDING MENGGUNAKAN SWOT DAN KTPPA (STUDI KASUS: PT MITRA SEKAWAN ULUNG) - Rahesya Putera Syailendra; Yelita Anggiane Iskandar (JURNAL TEKNOLOGIA, 2022)
According to PT Mitra Sekawan Ulung, a freight forwarding company in Indonesia, the number of customers from January to October 2020 continued to decrease. Although export and import activities at the end of 2020 slowly started to increase, in February 2021 the number of customers fell again which lasted until July 2021 therefore it is needed to analyze the marketing strategies related to export-import activities at the company. The purpose of this study is to determine the right marketing strategy and analyze the impact of implementing the strategic recommendations in the company. This research was conducted using the Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis method and the Kepner-Tregoe Potential Problem Analysis (KTPPA). The SWOT analysis was carried out based on field study observations related to internal and external factors of PT Mitra Sekawan Ulung which later the SWOT identification results were used to make a questionnaire. The results showed that the calculation for the x-coordinate (S-W) was 1.171 while the y-coordinate (O-T) was -0.929 so that the plotting strategy was obtained in quadrant-4 or the ST strategy (Strengths-Threats). ST strategy recommendations are manifested in recommendations for companies to start using social media as promotional media and create an official company website to introduce available information and services in the hope that the company's selling power in the export-import service business market can be increased.